Appraisal of the Geriatric Centre University College Hospital Ibadan. (2021)
Geriatric medicine is an emerging subspecialty in Nigeria. The interest in the care of older Nigerians followed the Madrid International Plan of Action on Ageing in April 2002. This led to an increase in research, publications and advocacy culminating in the establishment of the pioneer geriatric centre in Nigeria in 2012. Since then, there has been an increase in capacity building, manpower development and institutionalization of geriatric care in Nigeria. This is an account of the evolution of the Chief Tony Anenih Geriatric Centre, University College Hospital, Ibadan (UCH). METHODS: We undertook the review of the history, structure and key service elements in the Geriatric Centre, UCH from January 1, 2013, to December 31, 2020. RESULTS: The number of patients rose from 2,559 in the first year to 19,300 by the end of 2020. The initial four multidisciplinary units increased to 12 over the review period. Likewise, the in-patient admission increased between the first year (122 patients) and 2020 (141 patients). The overall mortality rate was 11.4% over the review period. Internship opportunities were provided to students including resident doctors, undergraduates (medical) and postgraduate students (Masters and PhD). Besides, 139 medical doctors have undergone the annual basic certificate training in geriatric medicine organised by the Centre. Also, 7 fellowship dissertations and 11 peer-reviewed papers have been published. CONCLUSION: The centre has demonstrated the possibility of caring for older patients in a low-resource setting. The employment of the multidisciplinary approach yielded a low mortality rate, higher attendance and manpower development.